71.5k views
2 votes
Solve dy/dx of y=(x-1)diveide(x+1)


Solve dy/dx of y=(x-1)diveide(x+1) ​-example-1

1 Answer

0 votes

I assume you're reffering to 5.b.

If


y = \left((x-1)/(x+1)\right)^(1/3)

then we can rewrite this as


y^3 = (x-1)/(x+1) \\\\ \ln(y^3) = \ln\left((x-1)/(x+1)\right) \\\\ 3\ln(y) = \ln(x-1) - \ln(x+1)

Now differentiate both sides implicitly:


(\mathrm d)/(\mathrm dx)\left[3\ln(y(x))\right] = (\mathrm d)/(\mathrm dx)\left[\ln(x-1)-\ln(x+1)\right] \\\\ \frac3{y(x)}(\mathrm dy)/(\mathrm dx) = \frac1{x-1} - \frac1{x+1} \\\\ (\mathrm dy)/(\mathrm dx) = \frac{y(x)}3\left(\frac1{x-1}-\frac1{x+1}\right) \\\\ (\mathrm dy)/(\mathrm dx) = \frac13 \left((x-1)/(x+1)\right)^(1/3) \left(\frac1{x-1}-\frac1{x+1}\right) \\\\ (\mathrm dy)/(\mathrm dx) = \boxed{\frac23 \frac1{x^2-1}\left((x-1)/(x+1)\right)^(1/3)}

User Arpit Shukla
by
5.5k points